Hubungan Antara Tingkat Pengetahuan dengan Sikap terhadap Narkoba pada Mahasiswa STIKes Persada Husada Indonesia Jakarta - Acep Setiawan; Agustina Agustina (STIKes Persada Husada Indonesia, 2016)
Narkoba or drugs is a materia /substance that can affect mental condition / psychologically (thoughts, feelings, and behavior,) and can cause physical and psychological dependence. Which is included in the drug are: narcotics, psychotropic and others addictive substances. Drugs an abbreviation of Narcotics and Drugs / hazardous materials that have been circulating in the communit y popular urban and rural, including for law enforcement officials. The design study is a descriptive study. This descriptive study aimed to find out the correlation between knowledge and attitude of students STIKes PHI against the dangers of smoking. The approach used in this study design was a cross sectional study in which data collection is done only once on each respondent. The number of samples obtained using formulas is equal to 84. Characteristics of respondents in the can through data collection consisted of five variables, such as age, gender, place of origin, religion, and Majors / semester. The results of this study are respondents aged over 20 years (66.7%), gender of respondents more men (56.0%) than women. The area of origin of respondents more than the area of West Kalimantan (75%). Religion 36.9% of respondents were Catholic. D-3 and S-1 student knowledge which 51.2% had poor knowledge about drugs. Student attitudes towards drug showed results of 58.3% had a positive attitude towards drugs. In this study showed a significant relationship between the variables knowledge with attitudes towards drugs, p-value = 0.024.